196k views
3 votes
Write the expression as a single logarithm 7log(x) y + 6 log(b) x

User Ofir Attal
by
6.4k points

1 Answer

3 votes

Answer:
log(x)^(7y)+log(b)^(6x)=log(x^(7y)b^(6x)).


Explanation:

Given logarithm expression


7log(x)^y + 6 log(b)^x.

We need to write it as a single logarithm expression.

First we need to apply exponent rule of logs to remove 7 and 6 in front of logs.


n log(p) = log(p)^n


7log(x)^y + 6 log(b)^x.= log(x)^(7y)+log(b)^(6x).

Now, we need to apply product rule of logs
log(p)+log(q) = log(pq).


log(x)^(7y)+log(b)^(6x)=log(x^(7y)b^(6x)).

Therefore, final answer is
log(x)^(7y)+log(b)^(6x)=log(x^(7y)b^(6x)).




User Nickornotto
by
6.0k points